Anticarcinogenic effect of gold nanoparticles synthesized from Albizia lebbeck on HCT-116 colon cancer cell lines - Harikrishna Malaikolundhan; Gowsik Mookkan; Gunasekaran Krishnamoorthi; Nirosha Matheswaran; Murad Alsawalha; Vishnu Priya Veeraraghavan; Surapaneni Krishna Mohan; Aiting Di (Artificial Cells, Nanomedicine, and Biotechnology)
Colon cancer is one of the major prevailing types of cancer worldwide. It has been the most important public health difficulty. Thus, we planned phytoconstituents arbitrated synthesis of gold nanoparticles (AuNPs) and examined their curative efficacy against the colon cancer (HCT-116) cells. In this current study, we formulated the AuNPs by using Albizia lebbeck (AL) aqueous leaf extract by the green method and synthesized AL-AuNPs were distinguished by UV-visible spectroscopy (UV-vis), energy dispersive X-ray diffraction (XRD), selected area (electron) diffraction (SAED) pattern, Fourier transform infrared spectroscopy (FTIR) and high-resolution transmission electron microscopy (HR-TEM). Synthesized AL-AuNPs confirmed by the UV absorption highest at 535 nm and the crystal structure of AL-AuNPs was additionally established by XRD and SAED pattern. HR-TEM images explained the size and morphology allocation of nanoparticles. FTIR analysis confirmed the presence of alkynes, aromatic compounds, and alkenes of biomolecules in AL-AuNPs. Furthermore, AL-AuNPs induced cytotoxicity at the IC50 concentration 48 µg/ml and also induced apoptosis by enhanced ROS production, decreased ΔΨm, apoptotic morphological changes by AO/EtBr and altering pro and anti-apoptotic protein expressions were analyzed in HCT-116 colon cancer cells. The findings of this investigation proved that the AL-AuNPs were revealed the potential anticancer activity against colon cancer (HCT-116) cells.